2020
DOI: 10.4068/cmj.2020.56.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Recovery Time after Sedation for Upper Gastrointestinal Endoscopy

Abstract: The purpose of this study was to investigate factors affecting recovery time after sedation for upper gastrointestinal endoscopy. The study population included 1310 patients in the national gastric cancer screening program who received sedation for upper gastrointestinal endoscopy from April 15, 2015 to December 31, 2018. Multivariate regression analysis was performed to identify factors related to recovery time. The mean recovery time after examination was 51.2 minutes (SD=13.3). Patients with a history of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…It was observed that BAI scores did not make a significant difference before the procedure, but after the procedure, BAI scores were calculated significantly higher in the group without sedation ( P < .001). Similar results were reported in the study conducted by Jin et al [ 12 ] In our study, significantly lower reporting of BAI scores after the procedure, we think that the higher patient comfort in procedures performed with sedoanalgesia and the fact that patients have prejudices about the procedure to be performed before the procedure affect these results.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that BAI scores did not make a significant difference before the procedure, but after the procedure, BAI scores were calculated significantly higher in the group without sedation ( P < .001). Similar results were reported in the study conducted by Jin et al [ 12 ] In our study, significantly lower reporting of BAI scores after the procedure, we think that the higher patient comfort in procedures performed with sedoanalgesia and the fact that patients have prejudices about the procedure to be performed before the procedure affect these results.…”
Section: Discussionsupporting
confidence: 91%
“…Recovery in elderly patients is more likely to be slow after endoscopic sedation [ 21 , 22 ], leading to prolonged hospital stay. Female sex was also an independent risk factor for delay.…”
Section: Discussionmentioning
confidence: 99%